Application of Integrative and Complementary Practices in children by physical therapists: a scoping review - Godoy , Débora Potenza Castro Rocha; Santos, Gabriel Xavier; Bastos, Rodrigo Almeida; Martinelli, Bruno; Peccin, Maria Stella; Mazzo, Alessandra (O Mundo da Saúde, 2026)
This study aimed to identify, synthesize, and analyze the available scientific knowledge on the use of integrative and complementary practices in pediatric physical therapy. A scoping review was conducted, with searches performed in the National Library of Medicine, SciVerse Scopus, Embase, Web of Science, and the Regional Portal of the BVS MTCI Americas, using specific descriptors defined based on the guiding question: “How have Integrative and Complementary Practices regulated by the Federal Council of Physical Therapy and Occupational Therapy been used in children within physical therapy?”. A total of 3,026 studies were identified, of which 43 comprised the final sample. The results indicated that most studies addressed manual therapies applied to specific pediatric conditions, with evidence of effectiveness and good acceptance. The most frequently used practices included body-based, manual, and meditative interventions, such as dance therapy, craniosacral therapy, and manual therapy, as well as approaches from Traditional Chinese Medicine, such as acupuncture and auriculotherapy, chiropractic, and osteopathy. It is concluded that Integrative and Complementary Practices have been widely incorporated into pediatric physical therapy treatment, demonstrating proven effectiveness and positive acceptance across different clinical settings.